Clinical utility of electronic alberta stroke program early computed tomography score software in the ENCHANTED trial database - Nagel, Simon (Stroke, 2018)
Background and Purpose: Clinical utility of electronic Alberta Stroke Program Early CT Score (e-ASPECTS), an automated system for quantifying signs of infarction, was evaluated in a large database of thrombolyzed patients with acute ischemic stroke. Methods: All baseline noncontrast computed tomographic scans of patients with anterior circulation acute ischemic stroke who participated in the alteplase dose arm of the randomized controlled trial ENCHANTED (Enhanced Control of Hypertension and Thrombolysis Stroke Study) were reviewed; poor quality and large (>6 mm) slice thickness were excluded. Included scans had e-ASPECTS scores correlated with baseline neurological severity (National Institutes of Health Stroke Scale scores) and 90-day disability outcomes (modified Rankin Scale scores). Multivariable logistic regression models were used to determine the predictive ability of e-ASPECTS for disability outcomes and symptomatic intracranial hemorrhage. Results: Of 2426 available computed tomographic images, 1480 (61%) were included in analyses of e-ASPECTS scores (median 9 [interquartile range, 8-10], 77% with good [range, 8-10] scores). Lower e-ASPECTS scores (per 1-point decrease) were significantly associated with increasing baseline National Institutes of Health Stroke Scale scores (r, −0.31; P<0.0001) and 90-day poor outcome (modified Rankin Scale scores, 2-6; r, −0.27; P<0.001). Adjusted odds ratios and 95% confidence intervals for 90-day outcomes were death or disability (modified Rankin Scale scores, 2-6; 0.91 [0.85-0.97]), death and major disability (modified Rankin Scale scores, 3-6; 0.89 [0.83-0.95]), and death (0.86 [0.79-0.95]); and for symptomatic intracranial hemorrhage, according to the Implementation of Thrombolysis in Stroke-Monitoring Study criteria was 0.87 (0.72-1.05). Conclusions: e-ASPECT scores from thin computed tomographic slices (≤6 mm) were highly correlated with baseline neurological severity and independently predict functional recovery and adverse outcomes in acute ischemic stroke.
Gesehen am 09.12.2019